2013
DOI: 10.1016/j.toxicon.2013.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of an undesired action of deguelin

Abstract: The pharmaceutical world has greatly benefited from the well-characterized structure-function relationships of toxins with endogenous biomolecules, such as ion-channels, receptors, and signaling molecules. Thus, therapeutics derived from toxins have been aggressively pursued. However, the multifunctional role of various toxins may lead to undesirable off-target effects, hindering their use as therapeutic agents. In this paper, we suggest that previously unsuccessful toxins (due to off-target effects) may be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…Complex I is involved in both oxidative phosphorylation and the phosphoenolpyruvate carboxykinase-succinate pathway, which could account for the increased gene expression in both respiratory pathways. The proposal that deguelin is a complex I inhibitor in H. contortus is consistent with previous results for mammalian cells (6,32,33) and with the current observation of a substantial increase in transcription linked to energy metabolism-related pathways-that is, oxidative phosphorylation, citric acid cycle, mitoribosome biosynthesis, and glycolysis-24 h before a significant reduction in worm motility, most likely reflecting a compensatory/negative feedback response to the inhibition of complex I. We tested this hypothesis by using a fluorescent dye that is sequestered by active mitochondria and assessed mitochondrial activity in response to various concentrations of deguelin at 48 h. Here, exposure of H. contortus to high concentrations of deguelin ablated the activity of mitochondria, whereas low concentrations of deguelin increased their activity, which supports the RNA sequencing results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Complex I is involved in both oxidative phosphorylation and the phosphoenolpyruvate carboxykinase-succinate pathway, which could account for the increased gene expression in both respiratory pathways. The proposal that deguelin is a complex I inhibitor in H. contortus is consistent with previous results for mammalian cells (6,32,33) and with the current observation of a substantial increase in transcription linked to energy metabolism-related pathways-that is, oxidative phosphorylation, citric acid cycle, mitoribosome biosynthesis, and glycolysis-24 h before a significant reduction in worm motility, most likely reflecting a compensatory/negative feedback response to the inhibition of complex I. We tested this hypothesis by using a fluorescent dye that is sequestered by active mitochondria and assessed mitochondrial activity in response to various concentrations of deguelin at 48 h. Here, exposure of H. contortus to high concentrations of deguelin ablated the activity of mitochondria, whereas low concentrations of deguelin increased their activity, which supports the RNA sequencing results.…”
Section: Discussionsupporting
confidence: 92%
“…Although most of the up-regulated pathways in deguelin-treated worms represent aerobic respiration, anaerobic pathways were also identified as being significantly up-regulated and associated with carbon fixation and glycolysis. On the basis of these findings and what is already known about the mode of action of deguelin in other organisms (6,32,33), we hypothesize that deguelin induces a loss in parasite viability, mainly by modulating or disrupting the function of the oxidative phosphorylation pathway, likely acting as a complex I inhibitor of the electron transport chain. Complex I is involved in both oxidative phosphorylation and the phosphoenolpyruvate carboxykinase-succinate pathway, which could account for the increased gene expression in both respiratory pathways.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…As a single agent, deguelin decreased cellular viability at higher doses (>1 µM), but inhibited the activities of some signaling molecules over a wide dosing range (0.1–10 µM). Unfortunately, treatment of deguelin at high dose exhibits undesirable side effects, such as respiratory depression and cardiotoxicity . Recently, a number of studies showed that low dose of deguelin (<1 µM) preserved its antitumor activity in triple‐negative breast cancer, lung cancer, colon cancer, and glioblastoma multiforme .…”
Section: Introductionmentioning
confidence: 99%